Integrative computational approaches identify haptoglobin inhibitors to modulate erythrocyte sedimentation rate in trauma-linked inflammatory and haematological malignancies - Al Khzem, Abdulaziz H.; Ahmad, Shaban (Frontiers in Chemistry, 2025)
Elevated levels of haptoglobin are commonly observed in conditions characterised by an increased erythrocyte sedimentation rate which are acute-phase reactants. These conditions include infection, trauma, inflammation, hepatitis, amyloidosis, collagen diseases, lymphoma, leukaemia, as well as obstructive and biliary diseases. However, no significant drugs are currently available to manage these conditions, making therapeutic intervention crucial effectively. In this study, we performed an extensive screening of the DrugBank database against the human haptoglobin protein (PDB ID: 4X0L) using High-Throughput Virtual Screening (HTVS), Standard Precision and Extra Precision (XP) docking methods, followed by pose processing with Molecular Mechanics Generalised Born Surface Area (MM/GBSA) calculations. This led to the identification of five potential inhibitors: L-histidinol phosphate (DB03997), L-gluconic acid (DB04304), 4-bromo-3-(carboxymethoxy)-5-(4-hydroxyphenyl)thiophene-2-carboxylic acid (DB07197), 3-O-methylfructose (DB02438), and glutamine hydroxamate (DB02446), with docking scores ranging from −7.96 to −5.58 kcal/mol and MM/GBSA scores between −26.23 and −1.00 kcal/mol. The study also included Density Functional Theory computations and pharmacokinetic profiling to assess these compounds’ suitability further, revealing promising results. Additionally, we conducted molecular interaction fingerprint analysis, revealing key residues involved in interactions, including 10LYS (Basic), 8LEU (non-polar), 7ASP (Acidic), and 7THR (Polar), indicating a mixed interaction profile. A 5 ns WaterMap analysis was used to identify optimal hydration sites and interaction patterns. Moreover, a 100 ns molecular dynamics (MD) simulation using the TIP3P water model in the NPT ensemble confirmed the stability of the protein-ligand complexes, with acceptable deviations, fluctuations, and intermolecular interactions. MM/GBSA calculations on the simulation trajectories supported these findings by providing binding free energy and complex energy estimations for all protein-ligand complexes. Although these findings provide compelling computational evidence for haptoglobin inhibition, experimental studies must confirm its effectiveness before human use.